Proton exchange membrane fuel cell membrane electrode catalyst slurry and dispersion process thereof

By adjusting the alcohol to water ratio in the catalyst slurry and controlling the dispersion temperature, the problem of difficult dispersion of the catalyst slurry and large internal resistance of the catalyst layer in the preparation of membrane electrodes is solved, efficient catalyst dispersion and performance improvement are achieved, and technical support is provided for the industrialization of fuel cells.

CN119601677AActive Publication Date: 2025-03-11WUXI WEIFU HIGH TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411712782.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

During the preparation of fuel cell membrane electrode, the catalyst slurry is difficult to disperse, the catalytic layer has large internal resistance and is prone to cracking, which limits the industrialization of fuel cells.

Method used

By adjusting the ratio of alcohol to water in the catalyst slurry, and precisely controlling the temperature during the dispersion process, optimizing the viscosity and rheological characteristics of the catalyst slurry, uniform dispersion of the catalyst is achieved.

Benefits of technology

It significantly improves the uniform dispersion and dispersion efficiency of the catalyst slurry, reduces the internal resistance of the catalytic layer, improves the performance of the membrane electrode, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601677A_ABST
    Figure CN119601677A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fuel cells, and particularly relates to a proton exchange membrane fuel cell membrane electrode catalyst slurry and a dispersion process thereof. The proton exchange membrane fuel cell membrane electrode catalyst slurry comprises a catalyst, a perfluorosulfonic acid resin solution, ultrapure water, isopropanol and ethanol, the catalyst adopts one or more of a platinum-carbon catalyst, a platinum-cobalt alloy catalyst and a ternary alloy catalyst, and the platinum loading capacity is 40-70%. According to the present invention, by adjusting the ratio of various alcohols to water in the catalyst slurry and ingeniously increasing the temperature of the catalyst slurry during the dispersion process, the accurate regulation of the slurry viscosity is achieved so as to ensure that the slurry can achieve the ideal rheological property during the dispersion process. The control strategy of adjusting the ratio of the alcohol to the water and optimizing the dispersion temperature not only promotes the uniform dispersion of the slurry, but also remarkably improves the dispersion efficiency, and no non-volatile substance is introduced, so that a solid foundation is provided for preparing a high-performance catalyst layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a proton exchange membrane fuel cell membrane electrode catalyst slurry and a dispersion process thereof. Background Art

[0002] PEMFC generates electricity through the electrochemical reaction of hydrogen and oxygen, and is highly efficient and environmentally friendly. Its core structure includes an anode, a cathode and a proton exchange membrane, in which the catalyst accelerates the electrochemical reaction, and the proton exchange membrane allows protons to pass through while preventing electrons from being directly transferred, thereby generating current.

[0003] Although fuel cell technology has been used in aerospace and other fields, its application in a wider range of fields is limited by factors such as cost, power density and life. At present, reducing the production cost of fuel cells is the key to promoting the large-scale application of fuel cells, and the performance and production process of the membrane electrode catalyst layer are crucial to the overall performance of the battery. However, there are problems such as difficult dispersion of catalyst slurry, large internal resistance of the catalyst layer and easy cracking in the membrane electrode preparation process. These challenges limit the industrialization of fuel cells.

[0004] In order to solve the problems of difficult dispersion of catalyst slurry, large internal resistance of the catalyst layer and easy cracking during the preparation of membrane electrode, the conventional method is to lower the dispersion temperature of the catalyst slurry and add anti-cracking agents, thickeners, conductive carbon nanotubes and other substances. However, low-temperature dispersion is not conducive to uniform dispersion of the resin, and external additives will affect the performance of the catalyst. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a proton exchange membrane fuel cell membrane electrode catalyst slurry and its dispersion process. The present invention achieves precise control of the viscosity of the catalyst slurry by adjusting the ratio of various alcohols to water in the catalyst slurry and cleverly increasing the temperature of the catalyst slurry during the dispersion process, thereby ensuring that the slurry can achieve ideal rheological properties during the dispersion process. This control strategy of adjusting the ratio of alcohol to water and optimizing the dispersion temperature not only promotes the uniform dispersion of the catalyst slurry, but also significantly improves the dispersion efficiency, and does not introduce non-volatile substances, providing a solid foundation for the preparation of a high-performance catalytic layer. In this way, we can ensure that the catalyst in each drop of slurry is fully dispersed, avoiding local uneven concentrations, thereby providing a more uniform reaction environment for the subsequent coating process. This fine control of the dispersion process is a key step in achieving efficient catalytic performance and is also the core of the technical innovation of the present invention.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: In the first aspect, an embodiment of the present invention provides a proton exchange membrane fuel cell membrane electrode catalyst slurry, including a catalyst, a perfluorosulfonic acid resin solution, ultrapure water, isopropanol and ethanol, wherein the catalyst is one or more of a platinum-carbon catalyst, a platinum-cobalt alloy catalyst and a ternary alloy catalyst, and the platinum loading is 40%-70%.

[0007] In a second aspect, an embodiment of the present invention provides a dispersion process of a proton exchange membrane fuel cell membrane electrode catalyst slurry as described in the first aspect, comprising the following steps: (1) Weigh a certain amount of catalyst, ultrapure water, isopropanol, ethanol and perfluorosulfonic acid resin solution and add them into a jacketed glass cup; (2) stirring the mixed solution of step (1) using a cantilever stirrer or a magnetic stirrer, and during the stirring process, warm water is introduced into the interlayer of the jacketed glass cup to keep it warm; (3) subjecting the catalyst mixture obtained in step (2) to high-speed shear dispersion, during which warm water is introduced into the interlayer of the jacketed glass cup for heat preservation; (4) stirring the catalyst slurry obtained in step (3), and during the stirring process, introducing warm water into the interlayer of the jacketed glass cup for heat preservation; (5) The catalyst slurry prepared in step (4) is stirred and cooled to 15-20°C for later use.

[0008] Furthermore, in step (1), the mass ratio of the ethanol to isopropanol is 1:10-200, and the mass ratio of the total mass of the ethanol and isopropanol to ultrapure water is 1-4:1.

[0009] Furthermore, the temperature of the warm water in steps (2), (3) and (4) is controlled at 30-50°C; The stirring speed in steps (2) and (4) is controlled at 200-350 rpm, and the stirring speed in step (3) is controlled at 8000-15000 rpm.

[0010] Furthermore, when a magnetic stirrer is used for stirring in step (2), a suitable magnet is placed in the jacketed glass cup in advance.

[0011] The technical solution provided by the embodiment of the present invention has the following beneficial effects: The present invention allows the perfluorosulfonic acid resin to be well dispersed in the solvent by precisely controlling the temperature of the catalyst slurry during the dispersion process (30°C-50°C), thereby forming a uniform coating on the catalyst. At the same time, the rheological properties of the catalyst slurry are optimized, and the viscosity is precisely controlled. The uniform dispersion of the catalyst slurry is significantly improved, the dispersion efficiency is improved, and a solid foundation is provided for the preparation of a high-performance catalytic layer.

[0012] Through this fine temperature regulation, the catalyst in the slurry is fully dispersed, effectively avoiding local concentration unevenness and creating a uniform reaction environment for the coating process. In addition, this method effectively reduces the internal resistance of the catalyst layer without increasing production costs, significantly improves the performance of the membrane electrode, and extends its service life.

[0013] The innovation of the present invention lies in the fine control of the dispersion process, which improves the microstructure of the catalytic layer, enhances the performance and efficiency of the fuel cell, and at the same time enhances its durability and reliability, providing technical support for the commercialization and large-scale application of fuel cell technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a performance comparison of the membrane electrode prepared with the catalyst slurry in Example 1 of the present invention and Comparative Example 1.

[0015] Figure 2 It is a performance comparison of the membrane electrode prepared with the catalyst slurry in Example 2 of the present invention and Comparative Example 1.

[0016] Figure 3 This is the performance of the membrane electrode prepared with the catalyst slurry in Comparative Example 2 of the present invention.

[0017] Figure 4 It is a comparison of rheological curves of the membrane electrode performance prepared with the catalyst slurry in Example 1 of the present invention and Comparative Example 1.

[0018] Figure 5 It is a performance comparison of the membrane electrode prepared by the catalyst slurry in Example 1 and Example 3 of the present invention. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0020] Example 1 A dispersion process for a proton exchange membrane fuel cell membrane electrode catalyst slurry comprises the following steps: (1) Weigh 5 g of catalyst (50% platinum-loaded platinum-carbon catalyst) and place it in a jacketed glass cup. Add 500 mL of deionized water, 5 mL of ethanol, 500 mL of isopropanol and 12.5 mL of D2020 perfluorosulfonic acid resin solution. Stir the mixture with a cantilever stirrer at a stirring speed of 300 rpm. Pass 40°C constant temperature water into the jacket. After stirring for 30 min, use a homogenizer to force disperse the mixture for 30 min at a speed of 10,000 rpm. (2) The dispersion in the jacketed glass cup was stirred with a cantilever stirrer at a stirring speed of 300 rpm, and constant temperature water at 40°C was introduced into the jacket to fully stir and disperse the dispersion to form a uniform catalyst slurry. The prepared catalyst slurry was stirred and cooled to 15°C-20°C to prevent sedimentation.

[0021] The catalyst slurry was applied to the front and back surfaces of the proton exchange membrane with an area of ​​130 mm × 280 mm by spraying (the sprayed catalyst layer was tested by XRF, and the anode loading was controlled to be 0.06 mg / cm 2 ; cathode loading 0.5mg / cm 2 ), and then the CCM is sealed with a frame, GDL is attached to form an MEA, and the MEA is placed in a battery fixture for performance and life test control tests. The performance curve is shown in the figure below. Figure 1 .

[0022] Example 2 A dispersion process for a proton exchange membrane fuel cell membrane electrode catalyst slurry comprises the following steps: (1) Weigh 5 g of catalyst (50% platinum-loaded platinum-carbon catalyst) and place it in a jacketed glass cup. Add 500 mL of deionized water, 50 mL of ethanol, 500 mL of isopropanol and 12.5 mL of D2020 perfluorosulfonic acid resin solution. Stir the mixture with a cantilever stirrer at a stirring speed of 300 rpm. Pass 50°C constant temperature water into the jacket. After stirring for 30 min, use a homogenizer to force disperse the mixture for 30 min at a speed of 10,000 rpm. (2) The dispersion in the jacketed glass cup was stirred with a cantilever stirrer at a stirring speed of 300 rpm, and constant temperature water at 50°C was introduced into the jacket to fully stir and disperse the dispersion to form a uniform catalyst slurry. The prepared catalyst slurry was stirred and cooled to 15-20°C to prevent sedimentation.

[0023] The catalyst slurry was applied to the front and back surfaces of the proton exchange membrane with an area of ​​130 mm × 280 mm by spraying (the sprayed catalyst layer was tested by XRF, and the anode loading was controlled to be 0.06 mg / cm 2 ; cathode loading 0.5mg / cm 2 ), and then the CCM is sealed with a frame, GDL is attached to form an MEA, and the MEA is placed in a battery fixture for performance and life test control tests. The performance curve is shown in the figure below. Figure 2 .

[0024] Example 3 A dispersion process for a proton exchange membrane fuel cell membrane electrode catalyst slurry comprises the following steps: (1) Weigh 5 g of catalyst (50% platinum-loaded platinum-carbon catalyst) and place it in a jacketed glass cup. Add 500 mL of deionized water, 10 mL of ethanol, 600 mL of isopropanol and 12.5 mL of D2020 perfluorosulfonic acid resin solution. Stir the mixture with a cantilever stirrer at a stirring speed of 300 rpm. Pass 40°C constant temperature water into the jacket. After stirring for 30 min, use a homogenizer to force disperse the mixture for 30 min at a speed of 10,000 rpm. (2) The dispersion in the jacketed glass cup was stirred with a cantilever stirrer at a stirring speed of 300 rpm, and constant temperature water at 40°C was introduced into the jacket to fully stir and disperse the dispersion to form a uniform catalyst slurry. The prepared catalyst slurry was stirred and cooled to 15°C-20°C to prevent sedimentation.

[0025] The catalyst slurry was applied to the front and back surfaces of the proton exchange membrane with an area of ​​130 mm × 280 mm by spraying (the sprayed catalyst layer was tested by XRF, and the anode loading was controlled to be 0.06 mg / cm 2 ; cathode loading 0.5mg / cm 2 ), and then the CCM is sealed with a frame, GDL is attached to form an MEA, and the MEA is placed in a battery fixture for performance and life test control tests. The performance curve is shown in the figure below. Figure 5 .

[0026] Comparative Example 1 A dispersion process for a proton exchange membrane fuel cell membrane electrode catalyst slurry comprises the following steps: (1) Weigh 5 g of catalyst (50% platinum-loaded platinum-carbon catalyst) and place it in a jacketed glass cup. Add 500 mL of deionized water, 5 mL of ethanol, 500 mL of isopropanol and 12.5 mL of D2020 perfluorosulfonic acid resin solution. Stir the mixture with a cantilever stirrer at a stirring speed of 300 rpm. Pass constant temperature water at 25°C into the jacket. After stirring for 30 minutes, use a homogenizer to force disperse the mixture for 30 minutes at a speed of 10,000 rpm. (2) The dispersion in the jacketed glass cup was stirred with a cantilever stirrer at a stirring speed of 300 rpm, and constant temperature water at 25°C was introduced into the jacket to fully stir and disperse the dispersion to form a uniform catalyst slurry.

[0027] The catalyst slurry was applied to the front and back surfaces of the proton exchange membrane with an area of ​​130 mm × 280 mm by spraying (the sprayed catalyst layer was tested by XRF, and the anode loading was controlled to be 0.06 mg / cm 2 ; cathode loading 0.5mg / cm 2), and drying. The CCM is sealed with a frame, GDL is attached to form an MEA, and placed in a battery fixture for performance testing and life test control tests. The performance curve is shown in the figure below. Figure 1 and Figure 2 .

[0028] Comparative Example 2 A dispersion process for a proton exchange membrane fuel cell membrane electrode catalyst slurry comprises the following steps: (1) Weigh 5 g of catalyst (50% platinum-loaded platinum-carbon catalyst) and place it in a jacketed glass cup. Add 500 mL of deionized water, 50 mL of ethanol, 500 mL of isopropanol and 12.5 mL of D2020 perfluorosulfonic acid resin solution. Stir the mixture with a cantilever stirrer at a stirring speed of 300 rpm. Pass 5°C constant temperature water into the jacket. After stirring for 30 min, use a homogenizer to force disperse the mixture for 30 min at a speed of 10,000 rpm. (2) The dispersion in the jacketed glass cup was stirred with a cantilever stirrer at a stirring speed of 300 rpm, and constant temperature water at 5°C was introduced into the jacket to fully stir and disperse the dispersion to form a uniform catalyst slurry. The prepared catalyst slurry was stirred and cooled to 15-20°C to prevent sedimentation.

[0029] The catalyst slurry was applied to the front and back surfaces of the proton exchange membrane with an area of ​​130 mm × 280 mm by spraying (the sprayed catalyst layer was tested by XRF, and the anode loading was controlled to be 0.06 mg / cm 2 ; cathode loading 0.5mg / cm 2 ), and drying. The CCM is sealed with a frame, GDL is attached to form an MEA, and placed in a battery fixture for performance testing and life test control tests. The performance curve is shown in the figure below. Figure 3 .

[0030] Examples 1-2 investigated the effect of slurry dispersion temperature of 40°C and 50°C on the performance of the prepared membrane electrode, and Comparative Examples 1-2 investigated the effect of slurry dispersion temperature of 25°C and 5°C on the performance of the prepared membrane electrode, and compared the performance of the membrane electrode prepared by the catalyst slurry in Example 1 and Comparative Example 1. Figure 1 The performance comparison of the membrane electrode prepared by the catalyst slurry in Example 2 and Comparative Example 1 is shown in Figure 2 As shown, the performance comparison of the membrane electrode prepared by the catalyst slurry in Comparative Example 2 is shown in Figure 3 As shown. Figure 1 , Figure 2 and Figure 3 It can be seen from the comparison that the membrane electrode prepared by the catalyst slurry in Examples 1 and 2 can effectively reduce the internal resistance of the membrane electrode catalyst layer and improve the performance of the membrane electrode.

[0031] Figure 4 The rheological curves of the membrane electrode prepared by the slurry dispersed at 40°C in Example 1 of the present invention and the room temperature in Comparative Example 1 are compared. It can be seen that the shear viscosity of the catalyst slurry prepared in Example 1 is higher than that of the catalyst slurry in Comparative Example 1, which shows that the dispersion process in Example 1 can improve the shear viscosity of the catalyst slurry. The higher the shear viscosity, the more stable the catalyst slurry is and it is not easy to settle. In addition, the shear viscosity does not change much with the change of shear rate, which shows that the prepared catalyst slurry has good rheological properties.

[0032] Figure 5 It is a performance comparison of the membrane electrodes prepared by the catalyst slurry in Example 1 and Example 3 of the present invention. It can be seen from the figure that the ratio of ethanol to isopropanol and the ratio of the total mass of ethanol and isopropanol to ultrapure water also have a certain influence on the performance of the prepared membrane electrode.

[0033] The catalyst slurry dispersion process of the present invention optimizes the viscosity of the catalyst slurry by precisely adjusting the dispersion temperature of the catalyst slurry, ensures the uniformity of dispersion, improves the dispersion efficiency, and provides a basis for preparing a high-performance catalyst layer. At the same time, it reduces the internal resistance of the catalyst layer, improves the performance of the membrane electrode, and extends the service life, providing technical advantages for the commercial application of fuel cells.

[0034] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A proton exchange membrane fuel cell membrane electrode catalyst slurry, characterized in that: The invention comprises a catalyst, a perfluorosulfonic acid resin solution, ultrapure water, isopropanol and ethanol. The catalyst is one or more of a platinum-carbon catalyst, a platinum-cobalt alloy catalyst and a ternary alloy catalyst, and the platinum loading is 40%-70%.

2. The dispersion process of the proton exchange membrane fuel cell membrane electrode catalyst slurry according to claim 1, characterized in that: The following steps are involved: (1) Weigh a certain amount of catalyst, ultrapure water, isopropanol, ethanol and perfluorosulfonic acid resin solution and add them into a jacketed glass cup; (2) stirring the mixed solution of step (1) using a cantilever stirrer or a magnetic stirrer, and during the stirring process, warm water is introduced into the interlayer of the jacketed glass cup to keep it warm; (3) subjecting the catalyst mixture obtained in step (2) to high-speed shear dispersion, during which warm water is introduced into the interlayer of the jacketed glass cup for heat preservation; (4) stirring the catalyst slurry obtained in step (3), and during the stirring process, introducing warm water into the interlayer of the jacketed glass cup for heat preservation; (5) The catalyst slurry prepared in step (4) is stirred and cooled to 15-20°C for later use.

3. The dispersion process of proton exchange membrane fuel cell membrane electrode catalyst slurry according to claim 2, characterized in that: In step (1), the mass ratio of the ethanol to isopropanol is 1:10-200, and the mass ratio of the total mass of the ethanol and isopropanol to ultrapure water is 1-4:

1.

4. The dispersion process of proton exchange membrane fuel cell membrane electrode catalyst slurry according to claim 2, characterized in that: The temperature of the warm water in steps (2), (3) and (4) is controlled at 30-50°C; The stirring speed in steps (2) and (4) is controlled at 200-350 rpm, and the stirring speed in step (3) is controlled at 8000-15000 rpm.

5. The dispersion process of proton exchange membrane fuel cell membrane electrode catalyst slurry according to claim 2, characterized in that: When a magnetic stirrer is used for stirring in step (2), a suitable magnet is placed in the jacketed glass cup in advance.

Citation Information

Patent Citations

  • Catalyst slurry, preparation method of catalyst slurry, and fuel cell

    CN110323460A

  • Catalyst slurry for fuel cell, preparation method thereof and membrane electrode

    CN111952611A

  • Preparation method of catalyst slurry suitable for ultrathin proton exchange membrane

    CN114373945A

  • Preparation method of fuel cell membrane electrode catalyst slurry

    CN117039016A

  • Preparation method of catalyst slurry for fuel cell membrane electrode

    CN117117213A